Reasons for and patterns relating to the extraction of permanent teeth in a subset of the Saudi population - Aleisa K; Khalil HS (Dove Medical Press, 2013)
Khalil Alesia,1 Hesham S Khalil2 1Department of Prosthetic Dental Sciences, 2Department of Oral and Maxillofacial Surgery, College of Dentistry, King Saud University, Saudi Arabia Background: The purpose of this study was to investigate the reasons for and patterns of extraction of permanent teeth in a subset of the Saudi population. Methods: During a 3-month period, dentists were asked to record, using a specially designed survey form, the reasons for every extraction of a permanent tooth. The reasons for tooth extraction were assigned to different causes, ie, dental caries, periodontal disease, eruption problems, trauma, orthodontics, failed root canal treatment, and others. The data requested for each extraction were: patient age, gender, nationality, and type of tooth removed and the reason for its extraction. Results: The highest percentage of extractions was observed in young females aged 10–30 years. Presence of caries was observed to be the main reason for extraction (50.2%) followed by orthodontic problems (18.2%), eruption problems (17.5%), and periodontal problems (8.2%). The most frequently extracted posterior teeth were the third mandibular molar (19.4%), the third maxillary molar (16.4%), the first maxillary premolar (13.2%), and the first mandibular molar (10.9%). Conclusion: Dental caries was found to be the most common reason for extraction of teeth. Molar teeth were found to be the most frequently extracted, with an increased number of extracted first premolars as a result of orthodontic treatment. The highest percentage of extractions was observed in young females aged 10–30 years. Keywords: extraction, Saudi, teeth, reasons, permanent